Solid-phase synthesis of anagrelide sulfonyl analogues - McMaster, Claire; Fülöpová, Veronika; Popa, Igor; Grepl, Martin; Soural, Miroslav (ACS combinatorial science, 2014)
Simple solid-phase synthesis of 3,10-dihydro-2H-benzo[e]imidazo[1,2-b][1,2,4]thiadiazin-2-one 5,5-dioxides is described, with Fmoc-α-amino acids and 2-nitrobenzenesulfonyl chlorides (2-NosCls) being the key building blocks. Fmoc-α-amino acids were immobilized on Wang resin and transformed to the corresponding 2-nitrobenzenesulfonamides in two steps. After reduction of the nitro group, Fmoc-thioureas were synthesized followed by cyclization of the 1,2,4-benzothiadiazine-1,1-dioxide scaffold with diisopropylcarbodiimide (DIC). Cleavage of the Fmoc protecting group followed by spontaneous cyclative cleavage gave the target products in excellent crude purity.
Keywords: techniky syntézy na pevné fázi; techniky kombinatorické chemie; fibrinolytika; Combinatorial Chemistry Techniques; Fibrinolytic Agents; cyklizace; Fluorenes; kyseliny sulfinové; Sulfinic Acids; Quinazolines; aminokyseliny; Cyclization; Solid-Phase Synthesis Techniques; Amino Acids; fluoreny; chinazoliny